STRUCTURE SHIFT ANALYSIS OF PASSIVE VOICE OF SHELDONâ€™S â€œTHE BEST LAIN PLANESâ€ TRANSLATED INTO SETYADIâ€™S â€œRENCANA PALING SEMPURNAâ€ - Liu, Xie Chun (Universitas Muhammadiyah Lampung, 2023)
In translating source language text (English) into target language test (Indonesian) will find some problems because of the different grammatical rules between them. One of the problems occur when translating English passive voice into Indonesia passive voice.Â This research focused on structure shifts. The object of research was the novel â€œThe Best Lain Plain by Shidey Sheldon as the Source Language Text (SLT) and its translation one â€œRencana Paling Setia by Setyadi as the Target langue Text (TLT). The research was done by qualitative method.Â The results of analysis were described not in number but in form of narration qualitatively. The results showed that the structure shifts occurred in translating passive voice of English as SL to Indonesian as TL.